CHANGES IN GILL HISTOLOGY AND MORTALITY RATE OF JUVENILE CASPIAN SEA BROWN TROUT (SALMO TRUTTA CASPIUS KESSLER, 1877) IN DIFFERENT WEIGHTS AND WATER SALINITIES - B. Ataei mehr; B. Majazi amiri; H. Abdolhai; A. Mirvaghegi (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2007)
Changes in gill histology and mortality rate of juvenile Caspian Sea Brown Trout Salmo trutta caspius Kessler-1877 in different weights and water salinities were studied. The indicators used in this study were the change in number and size of gill chloride cells as well as mortality rate of the juvenile trout. Juveniles weighing 2, 5, 10, 15 and 20 grams were directly transferred into water with salinities of 0, 4, 8 and 12.5 gr/lit and kept for 120 hours. Histological assessment showed that the number of gill chloride cells increases with the increase in weight and their size increases invisibly. Also, we found that the number of gill chloride cells is increased when salinity increases while the size of the cells undergoes an invisible downward trend. During the 120 hour test, mortality rate of the juveniles weighing 2 to 20 grams was zero in water salinities ranging 0 to 12.5 gr/lit. This supports the fact that the fish have a remarkable adaptability to changes in the environmental condition. Considering changes in the histology and mortality rate, it is concluded that the proper weight for release of juvenile Caspian Sea Brown Trout is 10 grams and the best water salinities is in the range 8-12.5gr/lit, the same value found in the estuary.